Soil Seed Bank of Two Karst Ecosystems in Bogor, Indonesia: Similarity with the Aboveground Vegeta-tion and Its Restoration Potential - Putri, Winda Utami; Qayim, Ibnul; Qadir, Abdul (Journal of Tropical Life Science, 2017)
Karst ecosystem in Bogor is currently threatened by mining activities. Restoration of the disturbed karst areas is urgently required. Seed banks are considered as an important potential seed sources for restoration. This study was conducted to quantify the composition and species diversity of the aboveground vegetation and the seed bank. The study determined the correspondence between the seed bank with the aboveground vegetation in relation with ecosystem restoration. Twenty 6 m × 6 m vegetation plots were established. A total of sixty soil samples were taken from the study sites. The seed bank was studied using germination experiment. All plant species in the vegetation plots and seedlings growing from all soil samples were identified and the number was counted to determine the composition, index of diversity, and index of similarity. There were 80 species from 41 families found in the seed bank in Mt. Nyungcung, dominated by Clidemia hirta (Melastomataceae), whereas 50 species from 29 families found in Mt. Kapur with Cecropia peltata (Urticaceae) dominated the site. Diversity index of Mt. Nyungcung and Mt. Kapur seed banks were 2.09 ± 0.21 and 1.78 ± 0.47 respectively. The similarity index between seed bank and the aboveground vegetation in the two study sites were 32.86% and 27.66% respectively. Mt. Nyungcung seed bank was more diverse than Mt. Kapur. The similarity between the seed bank with the aboveground vegetation in the two study sites were low. Further assessment is needed to determine the role of the seed bank of Mt. Nyungcung and Mt. Kapur in the restoration of the ecosystems.